Perancangan Sistem Penjualan Barang di CV Gunung Emas - Dewa Made Marta Aditama; I Gusti Agung Gede Putra Adhyatmika (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2022)
Sales process on CV. Gunung Emas is still done manually, that is, buyers have to come directly to the store to make the purchase process. In addition, the manual purchasing process is also time consuming, so there can be delays in needing more time for the goods to be sent and errors may occur when mentioning the product name, quantity, and address provided. Based on the above background, the formulation of the problem in this research is How to Design and Build a Sales System on CV. Gunung Emas, while the research objective to be achieved in the report preparation process is to be able to design and build a company sales system. The results of this study, namely to produce a sales system that aims to assist buyers in selecting and processing the desired product.